Management of BMI Is a Potential New Approach for the Prevention of Idiopathic Pulmonary Fibrosis - Ma, Yuchao; Feng, Chang; Tang, Haibo; Deng, Peizhi; Li, Yalan; Wang, Jie; Zhu, Shaihong; Zhu, Liyong (Frontiers in Genetics, 2022)
Aims: Current idiopathic pulmonary fibrosis (IPF) therapies usually show a poor outcome or treatment efficacy. The search for new risk factors has significant implications in preventing, delaying, and treating IPF. The association between obesity and the risk of IPF is not clear. This study aimed to investigate the role of different obesity types in IPF risk, which provides the possibility of weight loss as a new approach for IPF prevention. Methods: We conducted a two-sample Mendelian randomization (MR) analysis to assess the causal effect of obesity on IPF risk. We collected summary data of genetically determined obesity-related traits, including body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) from large-scale consortia (the sample size ranging from 232,101 to 681,275), and genetic association with IPF from one of the largest meta-analyses including 2,668 cases. A total of 35 to 469 single nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs) for obesity-related traits. We further performed multivariable MR to estimate the independent effect of BMI and WC on the risk of IPF. Results: Increased BMI and WC were associated with higher risk of IPF [OR = 1.51, 95% CI (1.22-1.87), p = 1.27 × 10−4, and OR = 1.71, 95% CI (1.08-2.72), p = 2.33 × 10−2, respectively]. Similar results for BMI and WC were obtained in the replicated analysis. Subsequently, only the result for BMI survived following the multiple testing correction and showed good consistency with the weighted median estimator. Sensitivity analyses indicated that there was no heterogeneity or horizontal pleiotropy for MR estimations. Further multivariable MR suggested that BMI showed the same direction and similar magnitude with that in univariable MR analysis. There was little evidence to support the causal role of WHR on the risk of IPF in this study. Conclusions: Genetically determined BMI demonstrates a causal risk for IPF, which offers a novel insight into probing potential mechanisms. Meanwhile, these results also suggest that weight loss may be beneficial to IPF prevention.